Economic Inequality and Human Development within the Framework of SDG 1 (No Poverty): The Impact of Poverty and Unemployment on the Human Development Index in West Papua (2015–2024) - Citra Marta Ayunda; Muhammad Abdul Ghofur; Harminingsih Harminingsih (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: West Papua, despite its rich natural resources, continues to experience a gap between economic growth and community welfare, as the quality of life of its residents has not fully improved. This study aims to analyze the effect of the open unemployment rate (OUR) and poverty rate on the Human Development Index (HDI) in West Papua Province during 2015–2024. Method: This research uses secondary data obtained from the West Papua Central Statistics Agency (BPS). Data analysis was performed using multiple linear regression with IBM SPSS Statistics software to test both partial and simultaneous effects. Results: The t-test results show that the open unemployment rate has a positive but insignificant effect on HDI (sig. 0.928 > 0.05), while the poverty rate has a negative and significant effect (sig. 0.001 < 0.05). The F-test confirms a significant simultaneous effect (F count = 16.042; sig. 0.002). The coefficient of determination (R²) of 0.821 indicates that 82.1% of HDI variation is influenced by OUR and poverty, while the remaining 17.9% is affected by other factors. These findings show that poverty is the most dominant factor influencing human development in West Papua. Novelty: The novelty of this study lies in its empirical focus on an under-researched region and its contribution to integrating local development issues with the global Sustainable Development Goals (SDG) framework, particularly SDG 1 (No Poverty), offering valuable insights for inclusive policy formulation.